Microbial transformation of andrographolide and medroxyprogesterone / Nur Asma Dalila Abdul Razak - Abdul Razak, Nur Asma Dalila (2015)
Microbial transformation has been known for a long time.The biotransformation allows the compound to be modified without the use of any chemical reagent and biotransformation act as a green chemistry. In this study, andrographolide and medroxyprogesterone have been used as a substrate that undergo fermentation with selected endophytes which are Aspergillus niger, Beauveria bassiana , R3-2SP17 , R3-3SP2, R3-3SP30, SC 24J, Cunninghamella elegans , Verticillium lecanii , SSW and Absidia coerulea . Method involved are media preparation, inoculation of fungi, feeding of substrate, incubation for 4 days and 8 days and extraction with ethyl acetate. The extracts were analyzed by HPLC to identify any biotransformation products.